UNDERSTANDING REGULATIONS OF ONLINE GAMBLING IN INDONESIA: Is It Forbidden? - Al Fatih, Sholahuddin; Nur, Asrul Ibrahim; Hermanto, Bagus; Haris, Haris (Fakultas Syariah, 2025)
This article examines the regulation of online gambling in Indonesia through both positive legal frameworks and religious fatwas issued by Islamic organisations such as the Indonesian Ulema Council (MUI), Muhammadiyah, and Nahdlatul Ulama (NU). The study employs a legal research method with statutory, conceptual, case-based, and comparative approaches. The findings suggest that the eradication of online gambling must be carried out comprehensively by strengthening digital content moderation mechanisms, as regulated under various Indonesian laws. Content moderation may include blocking, reducing visibility, delisting, and adjusting content ranking systems. A critical first step is the enactment of a Cybersecurity and Resilience Law that positions content moderation as a primary tool to safeguard Indonesia’s digital sovereignty. In this context, fatwas from Islamic organisations play a strategic role in reinforcing moral and social dimensions in combating online gambling. The elimination of online gambling is an integral part of Indonesia's efforts to realise digital sovereignty, which remains vulnerable to foreign interference. The study recommends further research in the form of comparative studies in Muslim-majority countries, focusing on how religious fatwas contribute to the fight against online gambling and how such approaches can be contextualised across jurisdictions. This article contributes to the development of an integrative framework that combines positive legal approaches with religious values in strengthening online gambling eradication policies in the digital era. Artikel ini mengkaji pengaturan judi online di Indonesia melalui perspektif hukum positif dan fatwa-fatwa yang dikeluarkan oleh organisasi keagamaan Islam, seperti Majelis Ulama Indonesia (MUI), Muhammadiyah, dan Nahdlatul Ulama (NU). Penelitian ini menggunakan metode penelitian hukum dengan pendekatan perundang-undangan, konseptual, kasus, dan perbandingan. Temuan studi ini menunjukkan bahwa pemberantasan judi online harus dilakukan secara komprehensif melalui penguatan mekanisme moderasi konten digital yang telah diatur dalam berbagai peraturan perundang-undangan di Indonesia. Moderasi konten dapat meliputi pemblokiran, penurunan visibilitas, delisting, dan sistem pemeringkatan konten. Langkah awal yang krusial adalah pembentukan Undang-Undang Keamanan dan Ketahanan Siber yang menjadikan moderasi konten sebagai instrumen utama untuk menjaga kedaulatan digital Indonesia. Dalam konteks ini, fatwa dari organisasi Islam memiliki peran strategis sebagai penguatan moral dan sosial dalam memerangi perjudian daring. Pemberantasan judi online merupakan bagian integral dari upaya mewujudkan kedaulatan digital Indonesia, yang saat ini masih rentan terhadap infiltrasi pihak asing. Penelitian ini merekomendasikan kajian lebih lanjut dalam bentuk studi perbandingan di negara-negara berpenduduk mayoritas Muslim mengenai kontribusi fatwa keagamaan dalam memberantas judi online, guna memperoleh pendekatan yang khas dan kontekstual di masing-masing negara. Artikel ini berkontribusi dalam memberikan kerangka pemikiran integratif antara pendekatan hukum positif dan nilai-nilai keagamaan dalam penguatan kebijakan penanggulangan judi daring di era digital.